Projeto e análise de um retificador híbrido trifásico com estratégia de controle para imposição de correntes de linha senoidais utilizando DSP TMS320F28335 - Rodrigues, Danillo Borges (2013)
Due to the considerable increase of electronic power processing devices in various segments of industry it becomes necessary to control and limit the current harmonic content injected into the distribution systems through the development of pre-regulator converters. In this context, this paper presents an analysis of a hybrid three-phase rectifier developed for power factor correction to be used as an utility interface of power electronics converters. The proposed structure is composed of an ordinary three-phase six-pulse diode-bridge rectifier (Graetz Bridge) with a parallel connection of single-phase SEPIC converters in each threephase rectifier leg. The main feature of the proposed structure is the power sharing technique which assures robustness, cost reduction and high reliability. In this work, is presented a complete discussion about the controlled rectifier s power contribution and also a complete analysis concerning the total harmonic distortion of current. Mathematical modeling analysis using state variables is presented. Experimental results of 5 kW laboratory prototype using DSP-based control technique are presented in order to corroborate with the theoretical analysis.